”Thomas Laurentii ex metropoli Finlandiae Abo” – Martin Crusiuksen päiväkirjamerkinnät Turun kirkkoherran vierailusta Tübingenissä 1585–1586 - Reima Välimäki (Finland, 2022)
English summary: The article presents an unknown source about the history of education and classical languages in sixteenth-century Finland. Thomas Laurentii, the parson of the Cathedral Church in the Evangelical diocese of Turku, visited the University of Tübingen and its famous professor of Greek, Martin Crusius in 1585–1586. Crusius recorded Thomas’s visit to several notes in his Diarium. These notes are in the unpublished parts of Crusius’s diary, and they are presented to the scholarship for the first time. An edition of the Latin source with a Finnish translation is provided in the appendix. Crusius’s diary challenges the earlier interpretation that has deemed Thomas Laurentii’s trip as a part of Swedish King Johan III’s ecclesiastical politics, namely his wish to establish good relationships to the patriarch of Constantinople. Although Thomas Laurentii travelled with the king’s blessing, his interaction with Martin Crusius pertains solely to learning the Greek language. When Thomas Laurentii travelled back to Kingdom of Sweden and his hometown Turku, he took with him several of Crusius’s works. Besides, he updated Martin Crusius’s information about Scandinavia and acted as a messenger between Crusius and the Swedish scholar Petrus Jonae, who had visited Crusius in 1582. Thus, the diary tells about the arrival of humanism in Finland and networks of information between sixteenth-century scholars in Northern Europe.